Could pool fire alone cause a domino effect? - Yang, R. (Elsevier Ltd, 2020)
The chain of accidents, also known as the domino effect, is responsible for several severe accidents in the chemical and process industries. The pool fire is often blamed as one of the primary accidents triggering a domino event. The present study is devoted to analyzing whether the pool fire alone can cause a domino event in processing and storage facilities. Two models, including a solid flame model and computational fluid dynamic model, are applied to simulate the escalation vector caused by a pool fire. The escalation vector probability is calculated using a probit model for a potential domino effect. This study also investigates the possible factors that can cause a domino effect and determine credible accident scenarios. The proposed concept of escalation vector and numerical models are tested using two past accidents. The study estimates the possibility of pool fires alone causing a domino effect. The results of this study show that although the pool fire alone has the ability to cause a domino event, it is unlikely to occur if a safe distance separates the equipment and proper mitigation measures are employed. Â© 2020 Elsevier Ltd